Long‐term outcomes after plaque incision and grafting for Peyronie's disease: comparison of porcine dermal and bovine pericardium grafts. (11th October 2020) - Fiorillo, Alessandro; Droghetti, Matteo; Palmisano, Franco; Bianchi, Lorenzo; Piazza, Pietro; Sadini, Paolo; Masetti, Martina; Molinaroli, Enrico; Gentile, Giorgio; Vagnoni, Valerio; Franceschelli, Alessandro; Colombo, Fulvio
Abstract: Background: Plaque incision and grafting (PEG) is one of the mainstays in surgical therapy for severe penile curvature in Peyronie's disease (PD). Different kinds of grafts are available for covering albugineal defects during PEG, both allografts and xenografts. However, to date, none of these proved superior to others. Objectives: To compare two different types of xenograft, porcine dermal matrix and bovine pericardium matrix in PEG for PD. Materials and methods: From 2010 to 2019, 63 patients with PD underwent PEG, using porcine dermal (n = 25; Group 1) and bovine pericardium (n = 38; Group 2) grafts. Long‐term outcomes were evaluated through multi‐disciplinary questionnaires administration by phone interview. The following items were considered: correction of penile bending, quality of erection, intercourse ability, penile shortening, and sensitiveness. Overall satisfaction and impact of surgery on sexual activity and quality of life were also investigated. Results: Plaque median (IQR) size was 29 (22‐33) mm and was smaller in Group 1 (27.5 vs. 31 mm; P  = .03). Complete follow‐up data were available for 53 patients (84%). Considering post‐operative outcomes, no differences were found when considering ED rates, penile shortening, sensitiveness, complications, and penile straightening (all P  > .1). Patients in Group 2 were more likely to have palpable penile nodules at follow‐up (20.6 vs. 0%; P  = .03). However, patient's post‐operative sexual life satisfaction was consistent between the two groups, with just 1 (5.3) and 8 (23.5) patients in Group 1 and 2 respectively referring a worsening in sexual life satisfaction ( P  = 0.2). At follow‐up, 84.9% of patients that would still undergo surgery for PD, with no statistical difference between the two groups ( P  = .4). Conclusions: Corporoplasty with PEG is an effective treatment for men with PD. Porcine dermal and bovine pericardium xenografts seem to have similar long‐term outcomes.